(untitled) (Research, Society and Development, 2021)
Introduction: There are several reasons associated with tooth loss that can trigger the need for multiple extractions, showing proven efficacy in the elimination of infectious foci and in maintaining the individual’s oral and general health. Upon losing teeth, the patient changes his speech, aesthetics, chewing and swallowing pattern, resulting in functional, social and psychological restrictions. Alveoloplasty is a surgical procedure that allows the plastic correction of the alveolar process, aiming to standardize the remaining bone tissue, allowing for the best prosthetic adaptation necessary after extractions. Objective: to report a clinical case of multiple extractions associated with alveoloplasty for prosthetic purposes and to show the importance of proper planning. Case report: The patient sought the dental clinic of a private educational institution, complaining of pain in the teeth when eating and lack of aesthetics when smiling. Clinical examination revealed the presence of root debris and teeth with mobility. The proposed treatment was to perform multiple extractions associated with surgery to regularize the alveolar ridge and later forward to prosthetic rehabilitation. The total upper mucosal supported dental prostheses and partial lower dentomucosal supported dentures were indicated for the case reported according to the patient’s need, financial condition and the possibility of treatment to be performed at the institution where the treatment was performed. Conclusion: Rehabilitation with dental prostheses has advantages, both in the functional realm, normalizing phonetics, and mainly, developing the masticatory function, as well as in the social realm, restoring aesthetics, restoring the individual’s smile and self-esteem.